Multidetector Computed Tomography in Post‐traumatic Ventricular Pseudoaneurysm - Bozlar, Ugur (Clin Cardiol, 2009)
We report a 20‐year‐old male with rare asymptomatic aneurysm of the left ventricle that was concluded to be a pseudoaneurysm given its calcified walls and the history of severe blunt chest trauma 8 years ago. Multidetector computed tomography (CT) angiography of the coronary vessels helped exclude vascular insult and suggest traumatic intramyocardial dissection as underlying etiopathogenesis, besides providing a good view of aneurysm and cardiac morphology in relation to coronary vessels. Copyright © 2009 Wiley Periodicals, Inc.